Inhibiting Solvent Co‐Intercalation in a Graphite Anode by a Localized High‐Concentration Electrolyte in Fast‐Charging Batteries - Jiang, Li‐Li; Yan, Chong; Yao, Yu‐Xing; Cai, Wenlong; Huang, Jia‐Qi; Zhang, Qiang (Angewandte Chemie International Edition, 2021)
Lithium‐ion batteries with routine carbonate electrolytes cannot exhibit satisfactory fast‐charging performance and lithium plating is widely observed at low temperatures. Herein we demonstrate that a localized high‐concentration electrolyte consisting of 1.5 M lithium bis(fluorosulfonyl)imide in dimethoxyethane with bis(2,2,2‐trifluoroethyl) ether as the diluent, enables fast‐charging of working batteries. A uniform and robust solid electrolyte interphase (SEI) can be achieved on graphite surface through the preferential decomposition of anions. The established SEI can significantly inhibit ether solvent co‐intercalation into graphite and achieve highly reversible Li+ intercalation/de‐intercalation. The graphite | Li cells exhibit fast‐charging potential (340 mAh g−1 at 0.2 C and 220 mAh g−1 at 4 C), excellent cycling stability (ca. 85.5 % initial capacity retention for 200 cycles at 4 C), and impressive low‐temperature performance. The unique solvation structure in a localized high‐concentration electrolyte can suppress co‐intercalation of ether solvent into the graphite interlayers and render fast‐charging of practical lithium‐ion batteries.